Developing a Classic Turn-Based RPG: The Making of 'Waduh! Aku Pergi Ke Isekai' with RPG Maker MV - Retno, Sujacka (Gameology and Multimedia Expert, 2024)
The game "Waduh! Aku Pergi ke Isekai" is a classic Role Playing Game (RPG) developed using RPG Maker MV. It tells the story of a young man named Makecar who is suddenly summoned to another world by a Goddess to defeat a Demon God threatening the world's destruction. The game combines classic RPG elements such as a Standard Turn-Based battle system, open-world exploration, and a variety of main and side quests, offering players diverse gameplay experiences. RPG Maker MV was chosen for its ease of use, even for beginner developers, utilizing a graphical user interface and simplified JavaScript scripting. Testing of the game shows that "Waduh! Aku Pergi ke Isekai" provides a deep and challenging gameplay experience, while also highlighting the potential of RPG Maker MV as an effective platform for independent game development. This game aims to inspire other game developers to create similar creative and original games.